Advancements in the Underlying Pathogenesis of Schizophrenia: Implications of DNA Methylation in Glial Cells - Chen, Xing-Shu; Huang, Nanxin; Michael, Namaka; Xiao, Lan (Frontiers in Cellular Neuroscience, 2015)
Schizophrenia (SZ）is a chronic and severe mental illness for which currently there is no cure. At present, the exact molecular mechanism involved in the underlying pathogenesis of SZ is unknown. The disease is thought to be caused by a combination of genetic, biological, psychological, and environmental factors. Recent studies have shown that epigenetic regulation is involved in SZ pathology. Specifically, DNA methylation, one of the earliest found epigenetic modifications, has been extensively linked to modulation of neuronal function, leading to psychiatric disorders such as SZ. However, increasing evidence indicates that glial cells, especially dysfunctional oligodendrocytes undergo DNA methylation changes that contribute to the pathogenesis of SZ. This review primarily focuses on DNA methylation involved in glial dysfunctions in SZ. Clarifying this mechanism may lead to the development of new therapeutic interventional strategies for the treatment of SZ and other illnesses by correcting abnormal methylation in glial cells.